2017
DOI: 10.1093/labmed/lmw060
|View full text |Cite
|
Sign up to set email alerts
|

A Simple PCR-RFLP Method for Genotyping ofIFNL4rs368234815 Polymorphism in Patients With Chronic Hepatitis C

Abstract: The PCR-RFLP method that we developed is accurate, rapid, inexpensive, and easy to perform for genotyping of the IFNL4 rs368234815 polymorphism. This method can be used for clinical and research work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…In the study of Sharafi et al on IL28B polymorphism to evaluate the response to hepatitis C treatment, they showed that the PCR‐RFLP technique was convenient to use and inexpensive. However, the method of sequencing is a standard and validated, but it is expensive and requires experienced technician …”
Section: Discussionmentioning
confidence: 99%
“…In the study of Sharafi et al on IL28B polymorphism to evaluate the response to hepatitis C treatment, they showed that the PCR‐RFLP technique was convenient to use and inexpensive. However, the method of sequencing is a standard and validated, but it is expensive and requires experienced technician …”
Section: Discussionmentioning
confidence: 99%
“…In this study, we applied the PCR_RFLP method for genotyping of rs368234815 polymorphism which was recently described by Pouryasin et al [25]. Among Iranian non-uremic patients with chronic HCV infection tested with this method, the rs368234815 ΔG/ΔG frequency was 17.3% [25]. Caucasian HD patients of Polish origin with persistently positive testing for HCV RNA revealed a similar frequency of the ΔG/ΔG genotype (16.1%).…”
Section: Discussionmentioning
confidence: 88%
“…Our paper for the first time describes associations between IFNL4 rs368234815 polymorphism and spontaneous HCV clearance in HD patients who substantially differ from the general population due to persistent uremic status and altered immune competence [34]. In this study, we applied the PCR_RFLP method for genotyping of rs368234815 polymorphism which was recently described by Pouryasin et al [25]. Among Iranian non-uremic patients with chronic HCV infection tested with this method, the rs368234815 ΔG/ΔG frequency was 17.3% [25].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Furthermore, both techniques have been used to differentiate many organisms to species level by the amplification of a conserved region of the mitochondrial D-loop, 11,12 ribosomal regions, 13,14 or other genetic loci. 15,16 However, although PCR-SSCP can be applied to any gene in any organism, PCR-RFLP has less spectrum superiority. Nevertheless, PCR-RFLP has attracted researchers' attention worldwide because of its low costs and does not require advanced instruments.…”
Section: Introductionmentioning
confidence: 99%